2016
DOI: 10.4081/rt.2017.6504
|View full text |Cite
|
Sign up to set email alerts
|

Myoepithelial Carcinoma of the Paracecal Mesentery: Aggressive Behavior of a Rare Neoplasm at an Unusual Anatomic Site

Abstract: Myoepithelial tumors of the soft tissues represent a rare group of neoplasms that vary in their clinical behavior, pathologic features and genetics. They are histopathologically typified by a myoepithelial immunohistochemical phenotype, of expression of one or more epithelial markers, S100 protein and smooth muscle actin. Because of their rarity and occurrence over a wide age range and at a variety of anatomic sites, they can be difficult to diagnose due to the lack of familiarity by physicians, which is compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Metastasis is commonly seen with these tumors. Nearly half of all diagnosed cases risk metastatic disease [1] , [5] , [18] . The most common site of metastasis is the lung, followed by lymph nodes, soft tissues and bone [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is commonly seen with these tumors. Nearly half of all diagnosed cases risk metastatic disease [1] , [5] , [18] . The most common site of metastasis is the lung, followed by lymph nodes, soft tissues and bone [1] .…”
Section: Discussionmentioning
confidence: 99%
“…CMCHNs have been observed in the gingiva, palate and tongue, larynx, parapharynx, nasopharynx, nasal cavity, nasal sinus, lacrimal gland, inferior temporal fossa, etc [17,18]. And literatures reported that approximately 75% of EMC [19,20] originated from the parotid gland, 10% from the submandibular gland, 10-15% from the salivary glands, and the remaining occurred in the palate, maxillary sinus, nasal cavity, trachea, and the root of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology examination of STM is challenging owing to microscopical diversity in cell morphology and types of stroma [ 3 , 12 ]. However, several studies showed that well-circumscribed margins and multinodular growth of spindled and plasmacytoid cells with eccentric nuclei in myxoid, hyalinized or chondroid stroma could be hallmarks for this benign tumor [ 3 , 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection with complete removal (R0 status) is a preferable treatment option of STM. Incomplete resection significantly increases risks of recurrence even in benign myoepitheliomas [ 3 , 12 ]. The vast majority of these tumors show a favorable prognosis and low incidence of distant metastases [ 3 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation